Multi premises network based on coding technique - Eltaif, Tawfig; Hamida, Belal Ahmed; S., Muwafu (2013)
In this article optical code division multiple access (OCDMA) was chosen as multiplexing technique because it’s considered as the next-generation optical access network. A multi premises downstream optical network was implemented using direct detection method based on OCDMA technique. The users encoded by modified prime code at C band with channel spacing 50 GHz. In this article low error rate transmission at high data rate for distances up to 25 km is demonstrated. Variation in the results was studied when varied fiber length, data rate and different effective power were applied. It has been shown that OCDMA is capable of providing gigabit-per-second for each user. Nevertheless, the results have indicated that direct detection OCDMA technique is capable to support multi premises network.